Program Pengenalan Hand-Only CPR Pada Siswa Dan Guru SD Negeri 37 Ampenan - Nantana, Lara Maras; Fitriani Restu Jayan Putri; Muhammad Abiansah; Muhammad Aras Alkadri; Muhamad Hendi; Abdul Majid (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Introduction to Hands-Only Cardiopulmonary Resuscitation (CPR) for Students and Teachers is an important step in increasing awareness and the ability to provide first aid in cases of sudden cardiac arrest occurring outside of a hospital, particularly in school environments. This socialization demonstrates that education and training on Hands-Only CPR, conducted using effective methods, can improve the skills of students and teachers in delivering basic life support to cardiac arrest patients. This socialization activity was attended by thirty students and teachers at Elementary School 37 Ampenan, Mataram City. The program included material presentations, demonstrations, a question and answer session, and hands-on practice using simple mannequins. The hands-on practice was conducted with the help of a rhythm song. Through this socialization, students were able to understand the main steps, such as correct and consistent chest compressions, and learn important emergency contact numbers. As a result of the Hands-Only CPR education, students were able to explain this first aid procedure to their peers in front of the class and contribute positively in emergency situations, as well as increase their confidence in taking action during a real emergency.